Varicose veins of lower extremities in pregnant women and birth outcomes - Bánhidy, Ferenc; Acs, Nándor; Puhó, Erzsébet H; Czeizel, Andrew E (Central European journal of public health, 2010)
The objective of the study was to estimate the association of pregnant women with varicose veins of lower extremities (VVLE) and the possible risk for adverse birth outcomes and among them different congenital abnormalities (CAs) in their children. Prospectively and medically recorded VVLE were evaluated in 332 pregnant women who delivered infants with CA (case group) and 566 pregnant women with VVLE who delivered infants without CA (control group) and matched to cases were compared in the population-based data set of the Hungarian Case-Control Surveillance System of Congenital Abnormalities, 1980-1996. About one-quarter of pregnant women had chronic VVLE while new onset VVLE occurred in the rest of pregnant women. There was no higher risk for adverse birth outcomes of pregnant women with VVLE, in fact the rate of preterm birth and low birth weight was somewhat lower than in the newborns of pregnant women without VVLE. The comparison of VVLE occurrence in pregnant women who had offspring with 21 different CA groups and in pregnant women who later delivered babies without CA showed a higher risk only for pectus excavatum, a mild CA. In conclusion, VVLE in pregnant women does not associate with obvious hazard for their fetuses.
Keywords: vrozené vady; dospělí; antikoagulancia; logistické modely; Female; Pregnancy Complications, Cardiovascular; novorozenec; Adult; ženské pohlaví; Logistic Models; Anticoagulants; lidé; Infant, Newborn; Hydroxyethylrutoside; Pregnancy Outcome; těhotenství; Congenital Abnormalities; studie případů a kontrol; hrudník vpáčený; Risk Factors; retrospektivní studie; prospektivní studie; Funnel Chest; Male; Case-Control Studies; Prospective Studies; varixy; výsledek těhotenství; rizikové faktory; Hungary; mužské pohlaví; Maďarsko; hydroxyethylrutosid; Pregnancy; Varicose Veins; Retrospective Studies; kardiovaskulární komplikace v těhotenství; Humans